Analysis of the selected antioxidant compounds n ice cream supplemented with Spirulina (Arthrospira platensis) extract - Szmejda, Klaudia; Duliński, Robert; Byczyński, Łukasz; Karbowski, Adrian; Florczyk, Tomasz; Żyła, Krzysztof (Wydawnictwo Politechniki Łódzkiej, 2018)
The research is aimed at evidencing that ice-cream formulations incorporating algae can have health-benefiting effects on human body. The main task of the project is to design ice-cream product line that distinguish itself from regular ice-cream by increased anti-oxidant activity resulted from inclusion of the algae extract. The currently known research evidences that ice-cream can be effective as carriers of health-promoting probiotic bacteria, which in turn encourages also application of other microorganisms in particular algae of specific strains (e.g. Spirulina platensis) as a supplement to ice-cream. In submitted research, the level of polyphenols and antioxidant activity expressed as degree of inhibiting generation of cationo-free radical from DPPH•+ solution were analyzed. Preliminary results based on antioxidative activity tests measured with potential to quench free radicals have shown that ice-cream formulations enriched with algae extract exhibit significantly higher potential achieving inhibition level of 39.7% in the mint ice cream samples as compared to 32.8% inhibition for the control sample without algae. Furthermore, each of the examined samples (dairy, pistachio, mint) ice creams versions supplemented with Spirulina were characterized by enhanced antioxidant activities expressed as potential to quench free radicals and the carotenoids content.
Keywords: ice creams; Spirulina; antioxidant.s.; lody; przeciwutleniacz.s.